Pengaruh Cognitive Load pada Pembelajaran Hanzi Menggunakan Metode Visual-Spatial - Aufa Shofiyana (Jurnal Pendidikan Ekonomi Undiksha, 2026)
Learning Hanzi often poses challenges for learners due to the complexity of its characters and the high demand for visual processing. This study aims to examine how cognitive load influences the effectiveness of Hanzi learning when the visual-spatial method is applied. Grounded in Cognitive Load Theory (CLT), this research explores the role of visual-based methods in managing intrinsic, extraneous, and germane load during the learning process. The findings indicate that the use of visual-spatial strategies can reduce irrelevant cognitive load and facilitate the development of more meaningful learning schemas. Moreover, this approach contributes to improved character comprehension and long-term retention. The results affirm that instructional designs utilizing visual representations can enhance cognitive efficiency and support the optimal internalization of Hanzi.